Quality of Life and Value Orientation of University Students in Middle-Adulthood - Čepelová Slávka; Barnová Silvia (Sciendo, 2020)
Introduction: Every person needs to define their own parameters of values and quality of life as there is a range of life circumstances and objective or subjective factors which force individuals to make decisions and select from available solutions depending on their personalities and other determinants. Currently, these notions have been broadly discussed and the authors of the presented study believe, that in the context of value orientation and life quality, there are new interactions, correlations and new truth to be revealed.